2006
DOI: 10.4049/jimmunol.176.2.949
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Gene Expression Profile of T Cells with the Splice Variants of TCRζ mRNA Observed in Systemic Lupus Erythematosus

Abstract: We have reported that the TCRζ mRNA with alternatively spliced 3′ UTR (ζ mRNA/as-3′-untranslated region (UTR)) and ζ mRNA lacking exon 7 (ζ mRNA/exon 7−) observed in systemic lupus erythematosus patient T cells can lead to down-regulation of both ζ and TCR/CD3 complexes. To determine whether these T cells expressing decreased ζ exhibit differential transcription patterns, we transfected retrovirus vectors containing wild-type ζ cDNA, ζ cDNA/as-3′ UTR, and ζ cDNA/exon 7− into murine T cell hybridoma MA5.8 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Among the up-regulated genes in T cell hybridoma MA5.8 cells transfected with CD3ζ chain mRNA splice-variant forms, the genes encoding cytotoxic molecules such as Gzma or MMP-11 were found. These proteins may be responsible for tissue damage [100]. Moreover, several molecules which account for lipid transport and metabolism, such as Pmm1, Lpn2, and Fads2, were also found to be increased in T cell hybridoma MA5.8 cells transfected with CD3ζ chain mRNA splice-variant forms.…”
Section: A Deficiency Of Cd3ζ Chain As One Of the Pathomechanisms Leamentioning
confidence: 87%
See 1 more Smart Citation
“…Among the up-regulated genes in T cell hybridoma MA5.8 cells transfected with CD3ζ chain mRNA splice-variant forms, the genes encoding cytotoxic molecules such as Gzma or MMP-11 were found. These proteins may be responsible for tissue damage [100]. Moreover, several molecules which account for lipid transport and metabolism, such as Pmm1, Lpn2, and Fads2, were also found to be increased in T cell hybridoma MA5.8 cells transfected with CD3ζ chain mRNA splice-variant forms.…”
Section: A Deficiency Of Cd3ζ Chain As One Of the Pathomechanisms Leamentioning
confidence: 87%
“…Tsuzaka et al [100] examined the gene expression profiles of T cell hybridoma MA5.8 cells expressing only either the splice variant of CD3ζ chain mRNA lacking exon 7 or CD3ζ chain mRNA with the short spliced variant of 3'UTR. The results showed that the genes encoding cytokines such as IL-2, IL-13, IL-15, IL-18, and transforming growth factor-β2, chemokines (CCL3, CCL5, CCL9, XCL1), and a chemokine receptor (CCR7) were down-regulated in these cells.…”
Section: A Deficiency Of Cd3ζ Chain As One Of the Pathomechanisms Leamentioning
confidence: 99%
“…Two mutants of the T-cell receptor chain have been linked to SLE, and overexpression of these unstable mutants in murine T-cells is associated with an eightfold increase in NDCBE transcripts in these cells (983). The cause and effect of this upregulation remains to be studied, although it has been noted that apoptosis of thymocytes, T-cell precursors, is increased by cellular alkalinization, yet is inhibited by stilbene derivatives, consistent with a proapoptotic action of NDCBE (980).…”
Section: Iii) Lymphatic and Immune Systems A) Increased Transcript Amentioning
confidence: 99%
“…To validate gene expression changes, quantitative realtime PCR was performed as described previously [9] with an Applied Biosystems Prism 7000 Sequence Detection System using TaqMan universal PCR master mix according to the manufacturer's procedure (Applied Biosystems Inc.) for the FasL gene. The TaqMan probes and primers for FasL (assay identification number Hs00181225_m1) were TaqMan Gene Expression Assays products (Applied Biosystems).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%